Menciptakan Bi’ah ‘Arabiyah di Lingkungan Universitas yang Multikultural - Miftachul Taubah (Universitas Yudharta Pasuruan, 2017)
Arabic area is an Arabic language environment which is a place where one interacts with others through the use of Arabic as a communication tool. The environment is the first facility for someone to obtain any language both mother tongue and second language. Arabic as a second (foreign) language can be obtained through the Arabic environment or known as bi'ah ‘arabiyah. This bi'ah is very important especially in realizing speaking skills in daily communication. This can be obtained formally or informally at certain levels of education. If these two environments do not exist then obtaining language skills will be difficult to achieve. Moreover, creating it in a multicultural University environment is not impossible, but a strong strategy and concern are needed to create the bi'ah ‘arabiyyah.